Fluorinated covalent organic frameworks for efficient drug delivery. Issue 48 (1st November 2022) - Ma, Baiwei; Xu, Yimeng; Hu, Fujia; Zhai, Lipeng; Huang, Yongyu; Qiao, Huijie; Xiong, Jiabin; Yang, Dehong; Ni, Zhihui; Zheng, Xiaofei; Mi, Liwei
Abstract : Two novel fluorinated covalent organic frameworks as drug carriers with good biocompatibility were developed, showing excellent drug loading capacity and sustained release in vitro . Abstract : In this study, two novel fluorine-functionalized crystalline covalent organic frameworks (COFs), namely DF-TAPB-COF and DF-TATB-COF, were synthesized, and their ordered structure, porosity, suitable pore size, and abundant fluorine groups were expected to serve as effective carriers in drug delivery. The excellent cell viability of DF-TAPB-COF and DF-TATB-COF was verified using MTT assays. Both COFs exhibited very high loading capacities in terms of drug loading performance, in particular the drug loading rate of DF-TAPB-COF for 5-fluorouracil (5-FU) was up to 69%. They also exhibited efficient drug release performance in a simulated body fluid environment. Cell endocytosis experiments demonstrated that DF-TAPB-COF and DF-TATB-COF could be effectively endocytosed by cells. Hence, this study offers new insight into the design and development of COF-based drug carrier systems.